Efflux-mediated tolerance to cationic biocides, a cause for concern?. Issue 11 (30th November 2022) - Wand, Matthew E.; Sutton, J. Mark
Abstract : Abstract With an increase in the number of isolates resistant to multiple antibiotics, infection control has become increasingly important to help combat the spread of multi-drug-resistant pathogens. An important component of this is through the use of disinfectants and antiseptics (biocides). Antibiotic resistance has been well studied in bacteria, but little is known about potential biocide resistance genes and there have been few reported outbreaks in hospitals resulting from a breakdown in biocide effectiveness. Development of increased tolerance to biocides has been thought to be more difficult due to the mode of action of biocides which affect multiple cellular targets compared with antibiotics. Very few genes which contribute towards increased biocide tolerance have been identified. However, the majority of those that have are components or regulators of different efflux pumps or genes which modulate membrane function/modification. This review will examine the role of efflux in increased tolerance towards biocides, focusing on cationic biocides and heavy metals against Gram-negative bacteria. As many efflux pumps which are upregulated by biocide presence also contribute towards an antimicrobial resistance phenotype, the role of these efflux pumps in cross-resistance to both other biocides and antibiotics will be explored.